Accumulation of Vesicle-Associated Human Tau in Distal Dendrites Drives Degeneration and Tau Secretion in an In Situ Cellular Tauopathy Model. (17th January 2012) - Lee, Sangmook; Kim, WonHee; Li, Zhihan; Hall, Garth F.
Abstract : We used a nontransgenic cellular tauopathy model in which individual giant neurons in the lamprey CNS (ABCs) overexpress human tau isoforms cell autonomously to characterize the still poorly understood consequences of disease-associated tau processing in situ . In this model, tau colocalizes with endogenous microtubules and is nontoxic when expressed at low levels, but is misprocessed by a toxicity-associated alternative pathway when expressed above levels that saturate dendritic microtubules, causing abnormally phosphorylated, vesicle-associated tau to accumulate in ABC distal dendrites. This causes localized microtubule loss and eventually dendritic degeneration, which is preceded by tau secretion to the extracellular space. This sequence is reiterated at successively more proximal dendritic locations over time, suggesting that tau-induced dendritic degeneration is driven by distal dendritic accumulation of hyperphosphorylated, vesicle-associated tau perpetuated by localized microtubule loss. The implications for the diagnosis and treatment of human disease are discussed.